American Red Cross first aid responding to emergencies. - American Red Cross (Yardley, PA StayWell, 2005)
First aid-responding to emergencies, fourth edition is the definitive text from which many schools teach first aid, CPR and AED skills. Through an integrated teaching approach using classroom lecture, simulated emergency situations, discussion and hands-on skill practice, The American Red Cross offers instructors and students the vital skills needed to save a life.
If not you, who? -- Responding to an emergency -- Before giving care -- Body systems -- Checking the victim -- Breathing emergencies -- Cardiac emergencies and unconscious choking -- Bleeding -- Shock -- Soft tissue injuries -- Musculoskeletal injuries -- Injuries to the extremities -- Injuries to the head, neck, and back -- Injuries to the chest, abdomen, and pelvis -- Sudden illness -- Poisoning -- Bites and stings -- Substance misuse and abuse -- Heat- and cold-related emergencies -- Reaching and moving victims in the water -- People with special needs -- Childbirth -- Delayed-help situations -- A safer and healthier life.
Includes bibliographical references and index
Keywords: First aid in illness and injury; Medical emergencies; Emergencies -- Programmed Instruction